A Survey of Brain Tumor Segmentation using Deep Neural Network - p, karuppasamy (International Journal of Reconfigurable and Embedded Systems (IJRES), 2021)
Tumor segmentation is an essential activity to providing intent way of predicting aggressiveness in medical image processing. Early identification of brain tumors plays a Significant part in making better treatment potential and increases the patient's lifetime. It is all important to segment the tumor, to protect healthy tissues during therapy. Manual segmentation is a complicated and prolonged procedure and improvement of automatic segmentation method afford proficient and intention segmentation. At present, automatic segmentation by means of deep learning methods proved the high-tech results. Deep learning methods for different kind of images provide robustness in segmentation. It refers to neural networks with many layers that extract a hierarchy of features from raw input images. This paper proposes to make another study of brain tumor segmentation along with the modern algorithms with current trends of deep learning algorithms are discussed.